Student character building - Damon, Georges H. (Beirut Hariri foundation, 2014)
The study asks many reflective questions in order to create a developmental framework for approaching character education based on historical research and practical applications of that research. An innovative program for student character building is to understand that successful schools are communities of individuals who trust each other to build understanding, collaboration and positive results.
: Chapter in a Book
Keywords: Character Education; Education de la personnalité